Right in Front of Our Eyes: The Hidden Curriculum and the Role of School-Based Practices on Violence Against Indigenous Women - Emily Fan (Journal of Advanced Research in Education, 2024)
As Indigenous issues begin to become an increasingly bigger part of the Canadian education system, the terms of their participation become a contentious issue amongst educators, especially in the wake of a human rights crisis (the Missing and Murdered Indigenous Women and Girls Movement). This paper explores the history of Indigenous education in Canada, the Missing and Murdered Indigenous Women and Girls movement, and the hidden curriculum in British Columbia’s Social Studies and Careers curriculum. Through a detailed analysis of the curriculum outlined by the British Columbian Ministry of Education, this paper aims to apply both traditional and modern educational theories to evaluate the effects of the education system upon both indigenous and non-indigenous students regarding the Missing and Murdered Indigenous Women and Girls movement. Based on its conclusions, the paper offers policy recommendations and further predictions on how the education system is expected to change in the near future.